Effect of aqueous red cabbage extract on uricase activity isolated from Pseudomonas aeruginosa - S.AL-Fayyadh, Mohannad (Iraqi Journal of Science, 2023)
Separation of uricase from Pseudomonas aeruginosa was done using (70%) satu-ration ammonium sulphate, and purification of this enzyme was done by ion ex-change chromatography on DEAE- cellulose column and eluted with linear NaCl (0-1M). Partial purified uricase gave an activity of (4.9 u/ml), protein concentration of (0.56 mg/ml), specific activity of (8.75 unit/mg) with purification folds (8.4) and a yield of (48%). The maximum purified uricase activity was detected at 35ºc and pH 8.5 with (0.12 mM.uric acid). The results shown that red cabbage extract (RCE) contain flavonoides which contain phenolic compounds and anthocyanines which glycoslated with mono or dimolecules of saccharides, while test for alkaloids, ster-oids, saponins and tannins were negative. Red cabbage extract (50mg/ml) have an inhibition activity against uricase compared with negative and positive control using allopurinol. So red cabbage considered as a novel inhibition for uricase whiel can used to treat gout disease in future